Investigating the Factors Influencing E-Book Acceptance Among Students from Less-Privileged Regions: A Case Study on Students of Shahrekord Universities - Ali Kheradmand; BiBi Eshrat Zamani; Zahra Babadi Akashe (Kerman University of Medical Sciences, 2019)
Background E-book is one of the forms of network publishing that has attracted extensive attention. Objectives The purpose of this study was to investigate the factors affecting the acceptance of e-books among students of less-privileged areas such as Shahrekord. Methods In this descriptive, analytical study, 371 students of Shahrekord University were selected through simple random sampling. The research instrument was a researcher-made questionnaire consisting of 48 questions that was designed with the help of research literature related to the technology acceptance model and interviews with five educational technology experts. Data were analyzed using ANOVA, Independent t-test, multiple regression and Pearson correlation tests. Results Cultural factors had a significant impact on users' attitudes and their use of e-books. A significant relationship was observed between the components of usefulness, ease of use, perceived enjoyment, cultural influences and attitude with the acceptance of e-books (P < 0.001). Also, the best predictors of acceptance and use of e-books were the components of perceived enjoyment, barriers, cultural influences, and attitudes. Conclusions The results regarding the identification of the factors affecting the acceptance of e-books can be used in virtual, non-formal and distance learning centers to design primary and supplementary educational resources. Design engineers and e-book providers can also use the findings of the current research to improve and promote electronic products.